Non-Surgical Treatment Success Rate for Nasolacrimal Duct Obstruction in Children up to Two Years of Age - Muhammad Amin, Muhammad Afzal Khan, Abdul Bari, Chakar Tajwidi, Nesr Farooq, Mehtab Mengal (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Congenital nasolacrimal duct obstruction (CNLDO) is a common condition where the nasolacrimal duct, which drains tears from the eye into the nasal cavity, is blocked at birth. Objective: To assess the non surgical treatment success rate for nasolacrimal duct obstruction in children up to two years of age. Study Design: Prospective interventional study Place and Duration of Study: Department of Ophthalmology, Teaching Hospital, Loralai from 1st February 2023 to 31st July 2023. Methodology: Fifty babies (54 eyes) under two years of age were enrolled. The children included were clinically diagnosed for persistent congenital nasolacrimal duct obstruction. The children were divided into four groups according to their age. Groups A to D were categorized as infants <6 months, between 6-12 months (older infants), between 12-18 months (toddlers) and between 18-24 months (older toddlers) respectively. The clinical symptoms including discharge history from one eye or both eyes, crusting, lid stickiness, mucopurulent discharge and redness were documented. All children were given non-surgical managing treatment comprising of Hydrostatic-Nasolacrimal Sac-Massage once a week through a well-trained clinician. In addition, topical antibiotic drops were prescribed to be applied whenever the mucopurulent discharge was presented. The regime was continued for six months and was discontinued only if the condition was treated. Results: The mean age of the children enrolled was 6.2±3.4 months. The clinical symptoms of children included 62% having mucopurulent discharge, 32% having epiphora, 4% mucocele and 2% having lacrimal abscess. The number of successful cases reported in children below 6 months was highest with a percentage of 81.81%. This was followed by children within the age group of 6-12 months having 81.25% success rate of non-surgical management of congenital nasolacrimal duct obstruction. The success rate declined with an increase in age with only 60% successful cases observed in children of 18-24 months. The non-surgical treatment success rate was analyzed as 77.77% ( 78%) for nasolacrimal duct obstruction in children up to two years of age. Conclusion: There were 77.77% of children who were successfully treated through non-surgical treatment success for nasolacrimal duct obstruction up to two years of age. Keywords: Non-surgical treatment, Success rate, Nasolacrimal duct obstruction.